Primary care heart failure service identifies a missed cohort of heart failure patients with reduced ejection fraction. (11th September 2021) - Kahn, Matthew; Grayson, Antony D; Chaggar, Parminder S; Ng Kam Chuen, Marie J; Scott, Alison; Hughes, Carol; Campbell, Niall G
Abstract: Aims: We explored whether a missed cohort of patients in the community with heart failure (HF) and left ventricular systolic dysfunction (LVSD) could be identified and receive treatment optimization through a primary care heart failure (PCHF) service. Methods and results: PCHF is a partnership between Inspira Health, National Health Service Cardiologists and Medtronic. The PCHF service uses retrospective clinical audit to identify patients requiring a prospective face-to-face consultation with a consultant cardiologist for clinical review of their HF management within primary care. The service is delivered via five phases: (i) system interrogation of general practitioner (GP) systems; (ii) clinical audit of medical records; (iii) patient invitation; (iv) consultant reviews; and (v) follow-up. A total of 78 GP practices (864 194 population) have participated. In total, 19 393 patients' records were audited. HF register was 9668 (prevalence 1.1%) with 6162 patients coded with LVSD (prevalence 0.7%). HF case finder identified 9725 additional patients to be audited of whom 2916 patients required LVSD codes adding to the patient medical record (47% increase in LVSD). Prevalence of HF with LVSD increased from 0.7% to 1.05%. A total of 662 patients were invited for consultant cardiologist review at their local GP practice. The service found that within primary care, 27% of HF patients identified for a cardiologist consultation were eligible for complex device therapy, 45% required medicines optimization, and 47% of patients audited required diagnosis codes adding to their GP record. Conclusion: A PCHF service can identify a missed cohort of patients with HF and LVSD, enabling the optimization of prognostic medication and an increase in device prescription. Graphical Abstract: